IDEAL-D: a rational framework for evaluating and regulating the use of medical devices - Sedrakyan, A; Campbell, B; Merino, J; Kuntz, R; Hirst, A; McCulloch, P (BMJ Publishing Group, 2016)
High profile device failures have highlighted the inadequacies of current regulation. Art Sedrakyan and colleagues call for a move to a graduated model of approval and suggest a framework to achieve this goal